Increasing socioeconomic disparities in tobacco smoking decline among French adolescents (2000–2017). (18th November 2019) - Janssen, Eric; Le Nézet, Olivier; Shah, Jalpa; Chyderiotis, Sandra; Brissot, Alex; Philippon, Antoine; Legleye, Stéphane; Spilka, Stanislas
Abstract: Background: This paper studies the evolution of transitions from first cigarette use to daily use by socioeconomic status (SES) among French adolescents over the course of 17 years, in a context of decreasing prevalence of tobacco use. Methods: A total of 182 266 adolescents participated in the nationally representative ESCAPAD survey at nine different time points between 2000 and 2017. Discrete time-event analysis was used to model the transition to daily cigarette use as a function of SES, gender, age at onset and the use of other psychoactive substances. Results: Although lifetime cigarette smoking and daily cigarette smoking decreased significantly over the studied time span, suggesting a positive impact of prevention policies, disadvantaged adolescents were consistently more prone to engage in daily cigarette smoking, more so in 2017 than 15 years earlier. In the same time span, transitions from initiation to daily cigarette smoking have shortened, with an accelerated pace among underprivileged adolescents. Conclusions: Accelerated transitions from initiation to daily cigarette use are a prevalent trend among disadvantaged adolescents in France. Efforts to mitigate the impact of marketing strategies and to promote health literacy should be pursued to reduce social inequalities in health.